An ANALYSIS OF THE APPLICATION OF EXPENSE FINES TOWARDS DELINQUENCY IN FINANCING OF QARDH AGREEMENTS ON MEMBERS AT KSPPS BMT AL HIKMAH SEMESTA, KALIAMAN BRANCH - Ningrum, Sinta Nadia; Wahidullah, Wahidullah; Nafisah, Zahrotun (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
The Sharia Savings and Loans Cooperative (KSPPS) BMT Al Hikmah Semesta plays an important role in providing financial access to communities that have not been reached by formal financial institutions. The main challenge that threatens the stability of the cooperative is late payment of financing. To overcome this problem, KSPPS uses a kifarat fine as a sharia-based method to encourage members to pay off their debts. The purpose of this study was to evaluate how effective the implementation of kifarat fines in qard agreements is and the impact on the financial behavior of members of the agreement. The results of the study, collected through in-depth interviews, indicate that kifarat fines can increase members' financial awareness and responsibility and encourage timely payments. However, some members oppose this policy, especially those who are facing financial difficulties. the implementation of kifarat fines must be in accordance with sharia principles by considering fairness, transparency, and the economic conditions of members. Financial education and a periodic evaluation system will support this policy. kifarat fines should be used not only as punishment, but also as a tool to teach and improve how to manage sharia microfinance.